APLIKASI PENGENALAN ALAT MUSIK TRADISIONAL SUMATERA SELATAN MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY - M. Fadhil Ramadhan Nurbani; Dewi Sartika; Juhaini Alie (Informatics Engineering, Faculty of Computer Science, 2023)
South Sumatra has several traditional musical instruments in the form of Burdah OKU, Gong, Kolintang, Flute, Gambus, Trumpet, Weaving, Genggong, Tambourine, Kenong Basemah. In this research, an application for recognizing traditional South Sumatran musical instruments has been designed and implemented by utilizing Augmented Reality technology. Augmented Reality is a combination of real objects and virtual objects that run interactively in real time. With the existence of technology in the form of Augmented Reality, it will facilitate the process of recognizing information and displaying objects of traditional musical instruments in South Sumatra. This research aims to help reintroduce residents to increase their knowledge of traditional musical instruments in South Sumatra. The software development method used to design and implement traditional musical instrument recognition applications is the Rational Unified Process method. Application testing is carried out using black-box testing and user testing. User testing was carried out by distributing questionnaires at Madrasah Ibtidaiyah Marfu'ah to grade 5 students. User satisfaction testing was calculated using a Likert scale and the results of the questionnaire questions obtained had a final score of 91% which was included in the strongly agree category